2019
DOI: 10.1002/ajpa.23986
|View full text |Cite
|
Sign up to set email alerts
|

Sources of variation in weaned age among wild chimpanzees in Gombe National Park, Tanzania

Abstract: Objectives:A key feature of human life history evolution is that modern humans wean their infants 2-4 years earlier on average than African apes. However, our understanding of weaning variation in apes remains limited. Here we provide the first such report in chimpanzees by examining weaned age variation using long-term data from Gombe National Park, Tanzania.Material and Methods: We analyzed 41 years of observational behavioral data from 65 offspring of 29 mothers to examine the relationships between weaned a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 60 publications
1
35
0
Order By: Relevance
“…Our findings do lend support to the idea that changes in bacterial diversity in infancy may be linked to lactation. We observed that the largest age-related shifts in gut microbial alpha-and beta-diversity correspond to typical ages at weaning 34,35 and that some of the indicator taxa in the microbiota of young infants are oligosaccharide specialists. However, the mechanistic link between lactation and diversity remains unclear.…”
Section: Discussionmentioning
confidence: 79%
“…Our findings do lend support to the idea that changes in bacterial diversity in infancy may be linked to lactation. We observed that the largest age-related shifts in gut microbial alpha-and beta-diversity correspond to typical ages at weaning 34,35 and that some of the indicator taxa in the microbiota of young infants are oligosaccharide specialists. However, the mechanistic link between lactation and diversity remains unclear.…”
Section: Discussionmentioning
confidence: 79%
“…Chimpanzee mothers are the primary carers for offspring, and close physical contact characterizes most of the first 2 years of life [ 38 ]. Offspring depend on their mother for nutrition through infancy until weaning between the ages of 3 and 5 years [ 39 , 40 ], but they continue to travel and socialize with their mother through the juvenile period, until at least the age of 8 years [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…If high ranking females are in better condition and/or have access to greater resources than low ranking females, then they may be able to wean offspring earlier. Finally, primate mothers may invest more in males if they are more costly to rear or because they have greater variance in reproductive success than females (Lonsdorf et al, 2020; Robbins et al, 2007).…”
Section: Introductionmentioning
confidence: 99%